2010
DOI: 10.1590/s1413-78522010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulinas 1-alfa e 1-beta na regeneração de nervos periféricos

Abstract: OBJETIVO: Avaliar o efeito das neuregulinas 1-alfa e 1-beta na regeneração de nervos ciáticos de camundongos C57BL/6J, adultos, machos, através da técnica de tubulização. MÉTODOS: Utilizaram-se 18 animais, divididos em 3 grupos, implantando-se prótese de polietileno em falhas de 4,0 mm no nervo ciático esquerdo: grupo 1 contendo apenas colágeno purificado (Vitrogen®); grupo 2, colágeno associado a neuregulina 1-alfa; grupo 3 com colágeno e neuregulina 1-beta. O grupo controle foi formado por 6 segmentos de ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The trend is similar also for NRG1β, but its expression is lower. These data are highly reminiscent of our previous observation (carried out on the distal portion of different experimental rat models: Crush injury and cut followed by end-to-end repair) where we found that NRG1α isoforms are more highly upregulated than NRG1β isoforms [17], thus reinforcing the idea that α isoforms also might play a role in nerve regeneration [50].…”
Section: Discussionsupporting
confidence: 87%
“…The trend is similar also for NRG1β, but its expression is lower. These data are highly reminiscent of our previous observation (carried out on the distal portion of different experimental rat models: Crush injury and cut followed by end-to-end repair) where we found that NRG1α isoforms are more highly upregulated than NRG1β isoforms [17], thus reinforcing the idea that α isoforms also might play a role in nerve regeneration [50].…”
Section: Discussionsupporting
confidence: 87%